Unraveling simultaneously enhanced open-circuit voltage and short-circuit current density in P3HT:ICBA:2, 3-pyridinediol blended film based photovoltaics. (8th April 2015) - Chang, Sheng Hsiung; Chiang, Chien-Hung; Tseng, Zong-Liang; Chiu, Kuo-Yuan; Tai, Chao-Yi; Wu, Chun-Guey
Abstract: A comprehensive study was carried out to understand the simultaneous enhancement of the open-circuit voltage and short-circuit current density in P3HT:ICBA:2, 3-pyridinediol blended film based photovoltaics. Femtosecond time-resolved photoluminescence, steady-state absorption spectrum, atomic force microscopy and 2D grazing-incidence wide-angle x-ray scattering were used to explore the transport characteristics of excitons. The comparatively faster exciton dissociation in the P3HT:ICBA:2, 3-pyridinediol blended film is attributed to the higher mobility of the excitons in P3HT. The space-charge limited-current measurements show the carrier mobility to be more balanced in the P3HT:ICBA:2, 3-pyridinediol blended film than in the P3HT:PCBM:2, 3-pyridinediol blended film, which is beneficial to the photo-induced current extraction. The enhanced short-circuit current density originates from the higher exciton dissociation yield in combination with the more balanced electron-hole mobility. The results should aid the design of an organic film for high-efficiency photovoltaics.